Neuroprotective Effect of Intrastriatal Caffeic Acid Phenethyl Ester Treatment in 6-OH Dopamine Model of Parkinson’s Disease in Rats - Burak Cem Soner; Eda Acikgoz; Salim Yalcin Inan; Sule Ayla; Ayse Saide Sahin; Gulperi Oktem (Parkinson's Disease)
Parkinson’s disease (PD) is the second most common neurodegenerative disorder, and the main cause of PD is still not known. Until now, no cure for Parkinson’s disease is yet in sight. Caffeic acid phenethyl ester (CAPE) is a polyphenolic component of the propolis, which can be derived from honeybee hive propolis. We aimed to determine the effect of intrastriatal CAPE administration as a neuroprotective agent on 6-hydroxydopamine (6-OHDA)-induced PD model. Adult male Wistar rats weighing 280–320 g were used. The PD model was induced with unilateral intrastriatal 6-OHDA injection. Treatment groups received 20 μmol/5 μL/4 day and 80 μmol/5 μL/4 day CAPE 24 h after 6-OHDA injection. Eight days after 6-OHDA application, behavioral studies (adhesive tape removal test, open-field test, cylinder test, and apomorphine-induced asymmetric rotational behavior) were performed once more to compare the effects of CAPE on behavior tests. Striatal histological verifications, immunohistochemistry, and stereological quantitation were performed. Our results for the first time showed that, besides improving the motor performance, CAPE treatment also prevents 6-OHDA-induced loss of TH-positive neurons. From our results, CAPE may be a promising clinical agent in the treatment of PD.